Kajian Proses Asuhan Gizi Terstandar (PAGT) Pada Pasien Hipertensi Di Rumah Sakit Umum Daerah Ende - Soro, Maria Fransisca; Talahatu, Anna Heny; Ndun, Helga J. N. (Faculty of Public Health, Nusa Cendana University, 2019)
The process of standardized nutrition care is an activity carried out on patients who are at risk of malnutrition, already experiencing malnutrition and special conditions with certain diseases. As for the steps of nutrition care process is namely nutrition assessment, diagnosis and intervention. Based on medical records at Ende Regional Hospital the number of inpatient hypertension patients was 442 in 2018. Nutrition services especially nutrition care process in hospital have been done well, but the implementation is still not optimal due to luck of nutritionists. This research was conducted to determine the process of standardized nutrition care in hypertensive patients in RSUD Ende. This research is a descriptive study with a qualitative approach. Informants key in this study are nutritionist and supporting informants is nutrition workers and hypertensive patients. The results of the study had been carried out well in Ende Regional Hospital,but the implementation was not optimal due to lack of nutritionists and nurses’ knowledge about nutrition. Standarduzed nutrition care can provide a good change for hypertensive patients, giving the right diet can reduce the hypertensive patient’s blood pressure. The results of this study are expected to further improve well-standarduzed nutrition care services to patients in accordance with the steps of nutrition care process so that it can help the healing process of disease.